Advancements in Wireless Sensor Networks for Industrial Automation - Singh, Nikhil (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 11 No 1&2 (2024): Journal of Advanced Research In Instrumentation Control Engineering, 2024)
In the realm of industrial automation, Wireless Sensor Networks (WSNs) have emerged as pivotal technologies, revolutionizing how industries monitor, control, and optimize their operations. These networks consist of spatially distributed autonomous sensors that wirelessly transmit data about physical and environmental conditions, facilitating real-time decision-making and proactive maintenance strategies. The evolution of WSNs has been driven by advancements in sensor miniaturization, energy efficiency, wireless communication protocols, and computing capabilities. Miniaturization has enabled the deployment of sensors in compact and hazardous industrial environments, enhancing monitoring capabilities while maintaining operational safety. Energy-efficient designs have extended sensor lifespans, reducing maintenance costs associated with battery replacements. Wireless communication protocols such as Zigbee, Bluetooth Low Energy (BLE), and Wi-Fi have enhanced data transmission reliability, speed, and range, meeting the stringent requirements of industrial automation. Furthermore, the integration of edge computing and fog computing technologies has brought computational capabilities closer to the data source, enabling real-time processing and reducing reliance on centralized cloud infrastructure. These advancements have expanded the applications of WSNs across industries, facilitating asset tracking, environmental monitoring, predictive maintenance, and process optimization. This article explores the advancements, applications, benefits, challenges, and future trends of Wireless Sensor Networks in industrial automation. By shedding light on these technologies, it underscores their transformative impact on industrial processes, paving the way for smarter, more connected industrial ecosystems that drive efficiency, sustainability, and competitiveness in the global market. Continued research and innovation will further refine WSN capabilities, addressing challenges and unlocking new opportunities for industrial automation. Understanding the evolution and integration of Wireless Sensor Networks is essential for industries seeking to leverage data-driven insights and technological advancements to optimize operations and maintain a competitive edge in today’s rapidly evolving industrial landscape.